Treatment of patients with metastatic colorectal cancer and poor performance status: current evidence and challenges (Clinics, 2019)
Patients with unresectable metastatic colorectal cancer live for a median of three years when treated with standard therapies. While the evidence guiding cancer-directed treatment of this disease comes from phase III trials that have mostly enrolled patients with good performance status, some patients present with poor clinical conditions. The best treatment for these patients remains to be determined. We performed a systematic review of the treatment outcomes of patients with metastatic colorectal cancer and poor performance status, defined as Eastern Cooperative Oncology Group performance status X2. Eligible articles were prospective or retrospective studies or case reports published in English, Portuguese or Spanish. We searched PubMed, EMBASE, LILACS and the Cochrane Library from onset until October 2017 using specific keywords for each search. We found a total of 18 publications, mostly case reports and retrospective studies (14 articles). One was an uncontrolled prospective trial, two were observational studies and one was an individual patient meta-analysis. Although some studies suggested benefits in terms of symptomatic response with standard chemotherapy, with good safety profiles when dose-reduced regimens were administered, a true survival gain could not be demonstrated. The scientific evidence for treating metastatic colorectal cancer patients with poor performance status is scarce, and more studies evaluating treatment for this population are necessary since this condition is not uncommon in clinical practice, particularly in the public healthcare system and developing countries and among destitute populations.